Utilization of information technology in the implementation of active learning in Muhammadiyah Private Schools 21 Dolok Batu Nanggar online - Tulus; Suwilo, Saib; Marpaung, T.J.; Elviwani (Talenta Publisher, 2020)
In general, junior high school students view mathematics as a difficult and boring subject. In addition to students, teachers also experience difficulties in delivering material, including time constraints in delivering quite a lot of material, and a lack of student interest in learning mathematics when using conventional learning methods such as from textbooks and explanations from the teacher. With these considerations, the proposer wants to apply knowledge and technology by making mathematics learning media tutorials so that they can increase understanding and attract students' interest in learning and help improve the quality of mathematics education and teaching. The result achieved is that community service for active learning and ICT should be reproduced because there are still many schools that have not implemented it. Meanwhile, from the progress of the times, namely Industry 4.0, ICT-based learning is very much needed.